Krāntadarśī Śibarāma - Pāla, Pratyuṣa,Dāśagupta, Dhīmāna (Setu Prakāśanīra Pakṣe, 2024)
Contributed articles on the works of Śibarāma Cakrabartī, 1903-1980, a great Bengali satirist.
Keywords: Aufsatzsammlung; Cakrabartī; Śibarāma; 1903-1980; Criticism and interpretation.